ANALISIS POSISI PASAR TERASI ZU-PER TERHADAP PRODUK PESAING DI KUALA PEMBUANG KABUPATEN SERUYAN - Rokhman Permadi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The purpose of this study was to analyze the characteristics of consumer shrimp paste and analyze the position of Zu-Per shrimp paste against competitors in Kuala Pembuang city. This study uses 65 respondents with an accidental sampling. Variable in this study is veriabel respondent characteristics and attributes (size, packaging, taste, purity, aroma, color, and price). respondent characteristic data were analyzed using descriptive analysis, while Zu-Per shrimp paste position against competitors analyzed using correspondence analysis (CA). Characteristics of respondents shrimp paste in Kuala Pembuang city of the age of majority is included in the cycle of life of older adults and middle age, the rate of primary and secondary education, it does not work (housewives) with an average predominant number of dependents as much as 2-4 person. Based on consumer perception Zu-Per paste has the advantage on the attributes of taste, purity, and color but have weaknesses on the attributes of size, packaging, flavoring, and price than the competitor's product paste.